FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN DISCHARGE PLANNING DIRUANG RAWAT INAP RUMAH SAKIT ISLAM IBNU SINA BUKITTINGGI TAHUN 2023 - Fitrina, Yossi; Andriani, Marlina; Sari, Gebi Mayang (STIKES Syedza Saintika Padang, 2023)
from when a patient receives health services until the patient feels ready to return to their environment.Thus, discharge planning is an action aimed at making the patient independent after discharge.Objectives : The purpose of this study was to determine the factors related to the implementation ofdischarge planning in the inpatient ward of RSI Ibnu Sina Bukittinggi in 2023. Methods : The designof this study was correlative descriptive with a cross sectional approach. The sample in this studywere 42 nurses in the inpatient room at RSI Ibnu Sina Bukittinggi using a random sampling techniquewith the chi square test. The research instrument uses a questionnaire and patientdocumentation/status.Results : The results of the univariate analysis showed that some nurses were not good at carryingout planning releases, namely 26.2%, having good communication, namely 73.8%, good involvementand participation, namely 73.8% and having a good time, 85.7%. The results of bivariate analysisobtained a P value (0.000) (<0.05).Conclusions : The conclusion, there is a significant relationship between the factors of communication,time, involvement and participation with other health workers and the implementation of the dischargeplan in the inpatient room at the Ibnu Sina Islamic Hospital, Bukittinggi.Discharge Planning, Communication, Time, Involvement and Participation